Geochemical and spectroscopic investigation of apatite in the Siilinjärvi carbonatite complex: Keys to understanding apatite forming processes and assessing potential for rare earth elements. (December 2020) - Decrée, Sophie; Savolainen, Mikko; Mercadier, Julien; Debaille, Vinciane; Höhn, Stefan; Frimmel, Hartwig; Baele, Jean-Marc
Abstract: The Siilinjärvi phosphate deposit (Finland) is hosted by an Archean carbonatite complex. The main body is composed of glimmerite, carbonatite and combinations thereof. It is surrounded by a well-developed fenitization zone. Almost all the rocks pertaining to the glimmerite-carbonatite series are considered for exploitation of phosphate. New petrological and in-situ geochemical as well as spectroscopic data obtained by cathodoluminescence, Raman and laser-induced breakdown spectroscopy make it possible to constrain the genesis and evolution of apatite through time. Apatite in the glimmerite-carbonatite series formed by igneous processes. An increase in rare earth elements (REE) content during apatite deposition can be explained by re-equilibration of early apatite (via sub-solidus diffusion at the magmatic stage) with a fresh carbonatitic magma enriched in these elements. This late carbonatite emplacement has been known as a major contributor to the overall P and REE endowment of the system and is likely connected to fenitization and alkali-rich fluids. These fluids - enriched in REE - would have interacted with apatite in the fenite, resulting in an increase in REE content through coupled dissolution–reprecipitation processes. Finally, a marked decrease in LREE is observed in apatite hosted by fenite. It highlights the alteration of apatite by a REE-poor fluid during a late-magmatic/hydrothermal stage. Regarding the potential for REE exploitation, geochemical data combined with an estimation of the reserves indicate a sub-economic potential of REE to be exploited as by-products of phosphate mining. Spectroscopic analyses further provide helpful data for exploration, by determining the P and REE distribution and the enrichment in carbonatite and within apatite. Highlights: This study focuses on apatite and its REE content at Siilinjärvi (Finland). Petrological and geochemical study helps deciphering its genesis. Igneous processes and metasomatic alteration are evidenced. A sub-economic potential of REE to be exploited as by-products is considered.